A Cislunar Economic Forecast under Public-Private Partnership - Naisha Chirag Naik (Space & Defense, 2026)
Cislunar space, spanning Earth’s orbit to the Moon, has emerged as a new frontier due to its strategic, scientific, and economic potential, with growing involvement from global powers, governments, and private entities diversifying the market. Unlike the first lunar space race, which saw a spike in activity amongst two countries followed by “silence,” the current cislunar era is hallmarked by a growing mix of public agencies, private companies, and international actors seeking to gain a foothold in what could be the foundation for a long-term space economy. While cislunar space was historically only an interest for superpowers, recent years have seen market diversification, with more countries and corporations involved on various levels of production and launch.